2021
DOI: 10.1097/sih.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Simulation in the Continuing Professional Development of Academic Emergency Physicians

Abstract: Introduction: Simulation is becoming a popular educational modality for physician continuing professional development (CPD). This study sought to characterize how simulation-based CPD (SBCPD) is being used in Canada and what academic emergency physicians (AEPs) desire in an SBCPD program. Methods: Two national surveys were conducted from March to June 2018. First, the SBCPD Needs Assessment Survey was administered online to all full-time AEPs across 9 Canadian academic emergency medicine (EM) sites. Second, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Comparatively, we estimate that our interactive virtual cases resulted in 40–50 distinct physicians completing online scenarios, and 15–25 participating in debriefs over a 9-month period, though exact numbers are unknown due to anonymous response collection. Previous studies have identified time limitations as a barrier to physician participation in simulation for continuing professional development [ 6 ]. Factors that likely contributed to our success in engaging participants include the focus on short scenarios (10–20 min), the flexibility to complete online cases anytime pre-debrief (44% were completed outside business hours and 15% overnight), and strategic topic selection involving rare scenarios and new/controversial guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, we estimate that our interactive virtual cases resulted in 40–50 distinct physicians completing online scenarios, and 15–25 participating in debriefs over a 9-month period, though exact numbers are unknown due to anonymous response collection. Previous studies have identified time limitations as a barrier to physician participation in simulation for continuing professional development [ 6 ]. Factors that likely contributed to our success in engaging participants include the focus on short scenarios (10–20 min), the flexibility to complete online cases anytime pre-debrief (44% were completed outside business hours and 15% overnight), and strategic topic selection involving rare scenarios and new/controversial guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation is an effective modality for health professions education [ 1 ] and in recent years has emerged as an important tool in Emergency Medicine for knowledge dissemination [ 2 , 3 ], system design [ 4 6 ], quality improvement [ 7 , 8 ], and continuing professional development [ 9 11 ]. Simulation offers, through deliberate practice, coaching, and feedback, an opportunity for healthcare professionals to undertake mastery learning, improving downstream outcomes that contribute to safer patient care [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…By 2016, an Aquifer (then MedU) collection of virtual patients was in use at approximately 75% (130) of those medical schools [14]. Furthermore, VPS is increasingly endorsed as an evidence-based, interactive learning format in continuing education for healthcare professionals [15].…”
Section: Introductionmentioning
confidence: 99%